1
$\begingroup$

I was reading this answer that shows how to calculate the inverse of public exponent, i got to the point where we apply the euclidean algorithm and finish substituting to get

(40−2×17)−1×(17−2×(40−2×17))=1

it states "this is a linear combination of 17 and 40, after simplifying you get:"

(−7)×17+3×40=1

which gives us the d = -7

but i'm stuck as to how we simplified down to

(−7)×17+3×40=1

from:

(40−2×17)−1×(17−2×(40−2×17))=1

i would be grateful if someone could explain it to me

Thanks in advance

$\endgroup$
1
$\begingroup$

Try just expanding the parentheses. Once they're all gone, collect all the multiples of $40$ and $17$ together:

$(40 - 2 \times 17) - 1 \times (17 - 2 \times (40 - 2 \times 17)) = 1$

$1\times40 - 2 \times 17 - 1 \times 17 + 2 \times (40 - 2 \times 17) = 1$

$1\times40 - 2 \times 17 - 1 \times 17 + 2 \times 40 - 4 \times 17 = 1$

$(1 + 2)\times40 - 2 \times 17 - 1 \times 17 - 4 \times 17 = 1$

$(1 + 2)\times40 - (2 + 1 + 4) \times 17 = 1$

$3\times40 - 7 \times 17 = 1$, or

$(-7) \times 17 + 3\times 40 = 1$

| improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.